R-T, Margaret, and the rats of nihm - Conly, Jane Leslie (New York: Collins Harper, 1990)
The further adventures of the intelligent young rat Rasco and his friends Christopher and Isabella as they try to ensure the survival of their secret community in the Thorn Valley after its accidental discovery by two human children.
English
Keywords: Conly, Jane Leslie; Rats and fiction